Answer:
y = 2x + 13
Step-by-step explanation:
y - 3 = 2 ( x + 5 )
y - 3 = 2x + 10
+ 3 + 3
y = 2x + 13
Answer:
256.8
Step-by-step explanation:
the tenths place is the first number after the decimal.
Answer:
1.5 + 1.3228756555323i
1.5 - 1.3228756555323i
Step-by-step explanation:
y = ax^2 + bx + c
a = 1, b = -3, c = 4
Using the quadractic formula:
![\frac{-b±\sqrt{b^2-4ac} }{2a} \\\\= \frac{3±\sqrt{9-4(1)(4)}}{2(1)}\\\\= \frac{3±2.64i}{2}\\\\= 1.5 ± 1.32](https://tex.z-dn.net/?f=%5Cfrac%7B-b%C2%B1%5Csqrt%7Bb%5E2-4ac%7D%20%7D%7B2a%7D%20%5C%5C%5C%5C%3D%20%5Cfrac%7B3%C2%B1%5Csqrt%7B9-4%281%29%284%29%7D%7D%7B2%281%29%7D%5C%5C%5C%5C%3D%20%5Cfrac%7B3%C2%B12.64i%7D%7B2%7D%5C%5C%5C%5C%3D%201.5%20%C2%B1%20%201.32)
Note: Kindly ignore the A in the above solution ^
Hence, there is no real solution. It has complex roots.
<em>Feel free to mark this as brainliest! :D</em>